Association Between Epilepsy and Leigh Syndrome With MT-ND3 Mutation, Particularly the m.10191T>C Point Mutation - Na, Ji-Hoon; Lee, Min Jung; Lee, Chul Ho; Lee, Young-Mock (Frontiers in Neurology, 2021)
Background and Purpose: Recent advances in molecular genetic testing have led to a rapid increase in the understanding of the genetics of Leigh syndrome. Several studies have suggested that Leigh syndrome with the MT-ND3 mutation is strongly associated with epilepsy. This study focused on the epilepsy-related characteristics of Leigh syndrome with the MT-ND3 mutation identified in a single tertiary hospital in South Korea. Methods: We selected 31 patients with mitochondrial DNA (mtDNA) mutations who were genetically diagnosed with mtDNA-associated Leigh syndrome. Among them, seven patients with MT-ND3 mutations were detected. We reviewed various clinical findings, such as laboratory findings, brain images, electroencephalography data, seizure types, seizure frequency, anti-epileptic drug use history, and current seizure status. Results: The nucleotide changes in the seven patients with the Leigh syndrome with MT-ND3 mutation were divided into two groups: m.10191 T>C and m.10158 T>C. Six of the seven patients were found to have m.10191 T>C mutations. The median value of the mutant load was 82.5%, ranging from 57.9% to 93.6%. No particular tendency was observed for the first symptom or seizure onset or mutant load. The six patients with an m.10191 T>C mutation were diagnosed with epilepsy. Three of these patients were diagnosed with Lennox-Gastaut syndrome (LGS). Conclusions: We reported a very strong association between epilepsy and the MT-ND3 mutation in Leigh syndrome, particularly the m.10191T> C mutation. The possibility of an association between the epilepsy phenotype of the m.10191T>C mutation and LGS was noted.